Dasar-Dasar Pendidikan Islam - Muiz Sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
Islamic education is based on five things, namely the Koran (which is the main source in Islamic teachings), as-Sunnah (words, deeds and approval of the Prophet for the words and deeds of his companions), the agreement of the scholars (ijma '), benefit people (mashalih al-mursalah), community traditions or habits ('urf) and ijtihad (the result of experts in Islam). The components that enable the educational process or the implementation of the educational process consist of at least 5 components, namely 1) educational objectives, 2) students, 3) educators, 4) educational content and 5) contexts that affect the atmosphere of education. The basic concept of Islamic education is the paradigm of the concept of Islamic education which has developed widely since long ago. In education we are familiar with three basic concepts of Islamic education, namely: ta'dib, tarbiyah, and ta'lim. Keyword: basic, education, Islam